2014
DOI: 10.1002/pola.27176
|View full text |Cite
|
Sign up to set email alerts
|

Soft template synthesis of donor–acceptor conjugated polymer nanoparticles: Structural effects, stability, and photothermal studies

Abstract: Donor-acceptor conjugated polymer nanoparticles and nanofibers, based on Poly[4,4-bis(2-ethylhexyl)-cyclopenta[2,1-b;3,4-b']dithiophene-2,6-diyl-alt22,1,3-benzoselenadiazole-4,7-diyl] (PCPDTBSe), were synthesized using Pluronic F127 as a template. The nanomaterials were compared to previously reported PCPDTBSe nanoparticles, which were synthesized without the use of a template. Our goal was to improve on the aqueous stability and photothermal heating efficiency of the previously synthesized PCPDTBSe nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
(146 reference statements)
0
29
0
Order By: Relevance
“…Syntheses 6 and 8 were chosen to best represent these groups respectively and then tested them in vitro to determine their cytocompatibility. The addition of surfactant Pluronic F127 to the collagen gel to help maintain dispersion of the nanoparticles most likely does not affect their morphology, as the concentration is very low (100 fold less than the amount of surfactant required for nanoparticle formation), and based on previous literature that conjugated polymer nanotubes and stable after formation and excess surfactant is inert . Figure shows that for the mouse cells, the particles show no difference from the control group regardless of the aspect ratio or 10‐fold difference in concentration tested.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Syntheses 6 and 8 were chosen to best represent these groups respectively and then tested them in vitro to determine their cytocompatibility. The addition of surfactant Pluronic F127 to the collagen gel to help maintain dispersion of the nanoparticles most likely does not affect their morphology, as the concentration is very low (100 fold less than the amount of surfactant required for nanoparticle formation), and based on previous literature that conjugated polymer nanotubes and stable after formation and excess surfactant is inert . Figure shows that for the mouse cells, the particles show no difference from the control group regardless of the aspect ratio or 10‐fold difference in concentration tested.…”
Section: Resultsmentioning
confidence: 88%
“…Although heat is generated by both types of PEDOT nanoparticles, and the NF actually have better infrared absorption than the NS, the NF are ineffective at reducing the number of viable cells compared to the NS. PEDOT NS may be most effective for photothermal cell killing as there is expected to be a higher number of nanoparticles to interface with the cells and transfer heat per mass amount compared to the NF . Greater reductions in cell viability might also be able to be achieved by increasing the laser power or increasing the concentration of PEDOT nanoparticles in the tissue phantoms.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has specialized in generating NIR absorbing nanoparticles derived from the donor‐acceptor polymer, poly[4,4‐bis(2‐ethylhexyl)cyclopenta[2,1‐b;3,4‐b′] dithiophene‐2,6‐diyl‐alt‐2,1,3‐benzoselenadiazole‐4,7‐diyl] (PCPDTBSe) . PCPDTBSe nanoparticles have been shown to have very low cytotoxicity at concentrations of 100 μg/ml and can provide ΔT = 30°C at concentrations of ∼30 μg/ml using 3.8 W/cm 2 800 nm light in vitro . However, PCPDTBSe nanoparticles do not have any detectable fluorescence, making them difficult to visualize in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insoluble complex templates with lamellar mesostructures were formed with a noble metal compound and a cationic surfactant such as CTAB [70]. Other surfactants that have been investigated include indigo carmine [71] and Pluronic ® F127 [72].…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%
“…In addition, insoluble complex templates with lamellar mesostructures were formed with a noble metal compound and a cationic surfactant such as CTAB [70]. Other surfactants that have been investigated include indigo carmine [71] and Pluronic ® F127 [72]. As a possible milestone for industrial fabrication of colloidal crystal templates, Choi et al [61] demonstrated an efficient method to fabricate large-area two-dimensional (2D) colloidal crystals as a template for nanopatterning of CPs; this method involves the electrophoretic deposition of negatively charged polystyrene colloidal particles and the assembly of the colloidal particles to 2D colloidal crystals at the air-water interface.…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%